Criminological Characteristics of Juvenile Aggression - PETECHEL, Oleksii Yu.; KERNIAKEVYCH-TANASIICHUK, Yuliia V.; VAZHYNSKYI, Volodymyr M.; KRASII, Mariia O. (Journal of Advanced Research in Law and Economics, 2019)
Active transformation of Ukrainian society has caused significant changes in political, economic, social spheres (transformation of the forms of production, decrease in the population's standard of living, changes in values). This in turn influences individual’s psychological sphere, the negative sides of which are intensification of the inner conflicts, increase in psychological tension, aggression, which may develop into severity. Due to the circumstances mentioned above the issue of exploring juvenile aggression and ways of its prevention are becoming relevant. The purpose of this article is to research the phenomenon of aggression, in particular juvenile aggression, and to propose the ways of its prevention based on the results of the research. The methodological framework for the research consist of the body of the scientific methods, general and specific, and the scientific method of learning. It is established that the issue of aggression is a multivariate one, which implies scientific research of different fields of human activity.In general, the prevention system against juvenile aggression shall have regard to the fundamental alterations in the consciousness of an individual, in particular learning the communication skills both with coevals and adults, development of skills of self-control, of the ability to make self-appraisement, increase of relevance of such appraisement, overcome of the personal negative formations, learning and realization of the non-aggressive forms of behavior.